2006
DOI: 10.1099/vir.0.81409-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on mucosal and intravenous transmission of simian immunodeficiency virus (SIVsm): the kinetics of evolution to neutralization resistance are related to progression rate of disease

Abstract: The kinetics of appearance of autologous neutralizing antibodies were studied in cynomolgus macaques infected with simian immunodeficiency virus (SIVsm) by the intravenous (IV) route (six monkeys) or the intrarectal (IR) route (ten monkeys). The SIVsm inoculum virus and reisolates obtained at 2 weeks, 3 or 4 months and later than 1 year were tested in a GHOST(3) cell line-based plaque-reduction assay with autologous sera collected at the same sampling times. All monkeys developed a neutralizing-antibody respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Since the standard deviation (SD) of intraassay variation was repeatedly found to be less than 10%, a 30% reduction in fluorescent PFU, corresponding to > 3 SD, was chosen as the cut-off. 37 Reduction of PFU by negative control plasma Ig, tested individually from six HIV-uninfected subjects, was repeatedly below 30% (data not shown).…”
Section: Neutralization Assay Using Ghost(3)-ccr5 Cellsmentioning
confidence: 93%
See 1 more Smart Citation
“…Since the standard deviation (SD) of intraassay variation was repeatedly found to be less than 10%, a 30% reduction in fluorescent PFU, corresponding to > 3 SD, was chosen as the cut-off. 37 Reduction of PFU by negative control plasma Ig, tested individually from six HIV-uninfected subjects, was repeatedly below 30% (data not shown).…”
Section: Neutralization Assay Using Ghost(3)-ccr5 Cellsmentioning
confidence: 93%
“…Three days after infection, green fluorescent expressing plaques were enumerated under the fluorescent microscope. Percentage neutralization was expressed as % plaque reduction in the virus cultures containing Ig relative to virus without sample Ig and calculated by the following formula 37 : Plaque reduction (%) = [1 -(PFU with sample Ig/PFU without sample Ig)] · 100. The cut-off for neutralization in this assay was based on intraassay variation, determined in three consecutive assays run on the same day.…”
Section: Neutralization Assay Using Ghost(3)-ccr5 Cellsmentioning
confidence: 99%
“…De novo antibodies were also generated against the escape variants in a pattern that recapitulates this process in HIV-1 infection [55,59,[77][78][79][80]. Lauren et al [81] also examined autologous neutralizing antibody responses against SIVsm in cynomolgus macaques. The authors found that each infected monkey developed a neutralizing antibody response against the inoculum virus; these responses developed earlier in the animals infected intravenously compared to those infected intrarectally.…”
Section: Antibody Neutralization Of Sivsm Envsmentioning
confidence: 98%
“…This prompted us to investigate these issues in our material consisting of 13 cynomolgus macaques with different disease patterns. Sequential SIVsm isolates that previously have been characterized for coreceptor use and neutralization sensitivity were available [30,31]. All isolates, but one, used CCR5 for cell entry, and CCR5 was also the major coreceptor in 70 out of 105 isolates tested.…”
Section: Introductionmentioning
confidence: 99%